Soluble single-site ruthenium-based polymer catalyst with intrinsic micropores as well as preparation method and application of soluble single-site ruthenium-based polymer catalyst
By using a ruthenium-based self-porous polymer catalyst with soluble unit points in the formic acid dehydrogenation catalyst, the problems of poor catalyst activity, low hydrogen production efficiency and difficulty in recovery are solved, and efficient and stable hydrogen production reaction of formic acid decomposition is achieved.
Patent Information
- Application Number
- CN202411550242.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing formic acid dehydrogenation catalysts have problems such as poor activity, low hydrogen production efficiency, poor stability and difficult recovery.
A ruthenium-based self-porous polymer catalyst with soluble unit points is used to form a DATPIM-Ru catalyst by coordination between the self-porous polymer support DATPIM and the active metal ruthenium, which is used to catalyze formic acid decomposition to produce hydrogen.
The stability of the high-active catalyst is improved, and the regeneration and recovery are carried out through dissolution and precipitation, which solves the stability and recovery problems of the catalyst and improves the hydrogen production efficiency of formic acid decomposition.
Smart Images

Figure CN119775550A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic polymer materials and catalysis, and specifically relates to a soluble single-site ruthenium-based self-microporous polymer catalyst and a preparation method and application thereof. Background Art
[0002] On the one hand, traditional energy sources such as coal, oil, and natural gas are non-renewable and increasingly depleted. On the other hand, their use will cause the emission of greenhouse gases and several gaseous pollutants, endangering the ecological environment. The need to develop clean and renewable new energy sources is becoming increasingly urgent. Hydrogen energy, as a clean and efficient energy source, is recognized as the most promising energy carrier for its pollution-free, wide source, high calorific value, rich application scenarios, and low ignition point. However, the volume energy density of hydrogen energy is very low, and it has the characteristics of low ignition point, wide explosion range, and large diffusion coefficient. Its safe storage and transportation has become a major bottleneck in the development and utilization of hydrogen energy, bringing huge challenges to researchers and researchers. Formic acid, as a low-cost, low-toxic, high-hydrogen content (590L / L; 4.4wt%), renewable and non-polluting material that can be well integrated into the closed loop of industrial production, has become one of the most ideal chemical hydrogen storage materials. The document Energy Fuels, 2023, 37, 1441-1450 clearly points out that formic acid as a hydrogen carrier has significant safety and economy compared with other carriers. The decomposition of formic acid to produce hydrogen cannot be separated from the help of catalysts. High-performance catalysts are the core of formic acid dehydrogenation. Formic acid dehydrogenation catalysts can be divided into homogeneous catalysts and heterogeneous catalysts.
[0003] However, heterogeneous catalysts are easy to recycle, but some of them have poor activity and low hydrogen production efficiency; homogeneous catalysts have problems such as poor stability, easy deactivation, and difficulty in recycling. Summary of the invention
[0004] The purpose of the present invention is to provide a soluble single-site ruthenium-based self-microporous polymer catalyst and its preparation method and application in order to solve the above-mentioned problems.
[0005] The technical scheme adopted by the present invention is as follows: a soluble single-site ruthenium-based self-microporous polymer catalyst, comprising: a self-microporous polymer carrier DATPIM and coordinated active metal ruthenium;
[0006] The DATPIM is a self-microporous polymer functionalized with 2,4-diamino-1,3,5-triazine (DAT) and has a chemical structure as shown in Formula I below:
[0007] Formula I:
[0008]
[0009] Wherein Ru3+ coordinates with the 2,4-diamino-1,3,5-triazine (DAT) functional group in DATPIM to form a DATPIM-Ru catalyst having a chemical structure shown in the following formula II:
[0010]
[0011] In a preferred embodiment, the DATPIM carrier is a soluble self-microporous polymer with a specific surface area of 30 to 2000 m 2 / g.
[0012] In a preferred embodiment, the mass fraction of ruthenium is 1% to 3%.
[0013] In a preferred embodiment, the mass fraction of ruthenium is 1.3%.
[0014] In a preferred embodiment, the preparation method of the soluble single-site ruthenium-based self-microporous polymer catalyst includes: mixing the self-microporous polymer PIM-1, dicyandiamide, and KOH in a mass ratio of 5:10:3, adding an appropriate amount of ethylene glycol monomethyl ether to dissolve, heating and stirring in a 423K oil bath at a speed of 500 rpm for 48 hours, cooling to room temperature, centrifuging the mixture, washing the obtained solid with hot water and hot methanol for several times, respectively, and placing the solid product in an oven at 100°C for 12 hours after solid-liquid separation to obtain DATPIM orange-yellow solid; dissolving DATPIM and RuCl3·H2O in dimethyl sulfoxide, wherein the mass fraction of metal ruthenium is 1.5wt%, stirring at room temperature for 24 hours, and then removing the solvent to obtain a DATPIM-Ru catalyst.
[0015] In a preferred embodiment, the soluble single-site ruthenium-based self-microporous polymer catalyst is used to catalyze the decomposition of formic acid to produce hydrogen. In the process of catalyzing the decomposition of formic acid to produce hydrogen, the reaction temperature is 363K, the pressure is normal, the solvent is dimethyl sulfoxide, triphenylphosphine is added, and the alkaline additive sodium formate is added.
[0016] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0017] 1. In the present invention, the self-microporous polymer has many advantages such as rich pore structure, high specific surface area, strong chemical modifiability, etc., and compared with other organic porous polymers, it has the unique advantage of being completely soluble in specific solvents. The ruthenium-based self-microporous polymer catalyst achieves high activity while enhancing the stability of the catalyst, and can be regenerated and recovered by dissolution and precipitation, realizing the complementary advantages of heterogeneous catalysts and homogeneous catalysis.
[0018] 2. In the present invention, the coordination of ruthenium metal with the specific functional groups of the self-microporous polymer realizes the unit point dispersion of ruthenium metal, which is conducive to making full use of precious metals and reducing costs. The catalyst preparation method and recovery method prepared by the present invention are simple to operate, have low requirements for equipment construction, and are easy to implement and promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the chemical structure of the catalyst carrier DATPIM in the present invention;
[0020] Figure 2 (a) is a schematic diagram showing the synthesis principle of DATPIM in the preparation process of the ruthenium-based self-microporous polymer catalyst DATPIM-Ru in the present invention;
[0021] Figure 2 (b) A schematic diagram of the synthesis principle of DATPIM-Ru during the preparation of the ruthenium-based self-microporous polymer catalyst DATPIM-Ru in the present invention;
[0022] Figure 3 is the infrared spectrum of DATPIM synthesized in Example 1 of the present invention;
[0023] Figure 4 is a N2 adsorption-desorption isotherm diagram of DATPIM synthesized in Example 1 of the present invention;
[0024] Figure 5 is a transmission electron microscope (TEM) image of the unit-point dispersed ruthenium-based self-microporous polymer catalyst DATPIM-Ru synthesized in Example 1 of the present invention;
[0025] Figure 6 It is a graph of gas production when 1 ml of formic acid is decomposed catalytically by DATPIM-Ru under different alkaline additive conditions in Examples 2 to 4. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] Reference Figure 1-6 ,
[0028] A soluble single-site ruthenium-based self-microporous polymer catalyst, a self-microporous polymer carrier DATPIM and coordinated active metal ruthenium;
[0029] DATPIM is a self-microporous polymer functionalized with 2,4-diamino-1,3,5-triazine (DAT) and has Figure 1Chemical structures shown:
[0030] Formula I:
[0031]
[0032] Wherein Ru3+ coordinates with the 2,4-diamino-1,3,5-triazine (DAT) functional group in DATPIM to form a DATPIM-Ru catalyst having a chemical structure shown in the following formula II:
[0033]
[0034] The DATPIM carrier is a soluble self-microporous polymer with a specific surface area of 30 to 2000 m 2 / g; the mass fraction of ruthenium is 1% to 3%.
[0035] The preparation method of the ruthenium-based self-microporous polymer catalyst comprises: mixing the self-microporous polymer PIM-1, dicyandiamide and KOH in a mass ratio of 5:10:3, adding an appropriate amount of ethylene glycol monomethyl ether to dissolve, heating and stirring (500 rpm) in an oil bath (423K) for 48 hours, cooling to room temperature, centrifuging the mixture, washing the obtained solid with hot water and hot methanol for several times, and drying the solid product in a 100°C oven for 12 hours after solid-liquid separation to obtain DATPIM orange-yellow solid. DATPIM and RuCl3·H2O are dissolved in dimethyl sulfoxide (DMSO), wherein the mass fraction of metal ruthenium is 1.5wt%, stirring at room temperature for 24 hours, and then removing the solvent to obtain a DATPIM-Ru catalyst.
[0036] The catalyst is used for catalyzing the decomposition of formic acid to produce hydrogen. In the process of catalyzing the decomposition of formic acid to produce hydrogen, the reaction temperature is 363K, the pressure is normal, the solvent is dimethyl sulfoxide, triphenylphosphine is added, and the alkaline additive is triethylamine, sodium hydroxide or sodium formate, preferably sodium formate.
[0037] A method for recovering a single-site dispersed ruthenium-based self-microporous polymer catalyst DATPIM-Ru for catalyzing formic acid to produce hydrogen, comprising: adding a poor solvent to a system after the reaction is completed, shaking to precipitate a solid and centrifuging it, then dissolving the separated solid with DMSO, adding a poor solvent again to precipitate it, washing, filtering, and drying after two dissolutions to obtain recovered DATPIM-Ru. The good solvent includes tetrahydrofuran, methanol, dichloromethane, chloroform, water, etc., preferably deionized water.
[0038] Embodiment 1:
[0039] A preparation method of a DATPIM-Ru catalyst comprises the following steps:
[0040] (1) Preparation of DATPIM: 100 mg of PIM-1, 200 mg of dicyandiamide, and 60 mg of KOH powder were added to a high-pressure glass sealed tube, and 20 ml of 2-methoxyethanol was added; after thorough ventilation with nitrogen, the tube was tightly sealed with a polytetrafluoroethylene cap, and heated (500 rpm) in an oil bath (423 K) for 48 hours. Subsequently, the system was cooled, the mixture was centrifuged, and the obtained solid was washed several times with hot water and hot methanol, respectively, collected by centrifugation, and dried in an oven at 100°C for 12 hours to obtain DATPIM orange-yellow solid.
[0041] (2) Preparation of DATPIM-Ru: 176 mg of DATPIM powder obtained in step (1) was placed in a 25 ml two-necked flask, 6 mg of RuCl3·H2O was added, and 5 ml of dimethyl sulfoxide (DMSO) solvent was added to dissolve the solid powder. The mixture was heated in an oil bath at 60°C with stirring for 5 h to obtain a DATPIM-Ru catalyst dissolved in DMSO.
[0042] (3) Deionized water is added to the mixed solution obtained in step (2) to precipitate the DATPIM-Ru catalyst, which is then washed and dried for later use.
[0043] Embodiment 2:
[0044] The DATPIM-Ru catalyst is used for formic acid catalytic hydrogen production, and triethylamine (Et3N) is used as an alkaline additive, including the following steps:
[0045] (1) Dissolve 80 g of sodium bicarbonate in 700 ml of water to prepare a saturated sodium bicarbonate solution for later use.
[0046] (2) Weigh 100 mg of the DATPIM-Ru catalyst obtained in Example 1 and dissolve it in DMSO solution, add 42 mg of triphenylphosphine, set the stirring rate to 500 rpm, and stir evenly.
[0047] (3) The system was placed in an oil bath and heated to 90°C. After stabilization for 15 minutes, 0.33 ml of triethylamine and 1 ml of formic acid were added into the system using a syringe. The generated gas was collected using the drainage method, and the change in gas production over time was recorded.
[0048] (4) After the gas production is completed, the catalyst turnover frequency (TOF) and formic acid decomposition rate are calculated.
[0049] Embodiment 3:
[0050] The DATPIM-Ru catalyst was used for formic acid catalytic hydrogen production, with NaOH as the alkaline additive, comprising the following steps: replacing the 0.33 ml triethylamine and 1 ml formic acid solution in step (3) of Example 2 with 1 ml formic acid / sodium hydroxide mixed solution containing 320 mg sodium hydroxide, and the other steps were the same as those in Example 2.
[0051] Embodiment 4:
[0052] The DATPIM-Ru catalyst is used for formic acid catalytic hydrogen production, and sodium formate is used as an alkaline additive, comprising the following steps: replacing the 0.33 ml triethylamine and 1 ml formic acid solution in step (3) of Example 2 with 1 ml formic acid / sodium formate mixed solution containing 600 mg sodium formate, and the other steps are the same as Example 2.
[0053] Embodiment 5:
[0054] A catalytic experiment of formic acid hydrogen production was carried out using a RuCl3·H2O catalyst that was not coordinated with DATPIM to form a control, including the following steps:
[0055] (1) Dissolve 80 g of sodium bicarbonate in 700 ml of water to prepare a saturated sodium bicarbonate solution for later use.
[0056] (2) Dissolve 6 mg of RuCl3·H2O in 5 ml of DMSO in a 25 ml two-necked flask.
[0057] Steps (3) and (4) are the same as those in Example 2.
[0058] Table 1. Summary of the performance of the single-site dispersed DATPIM-Ru catalysts prepared in Examples 2 to 5 for catalytic hydrogen production from formic acid
[0059]
[0060] From the results in Table 1, it can be seen that the DATPIM-Ru catalyst can significantly improve the efficiency of hydrogen production from formic acid decomposition, especially the catalytic system with the addition of sodium formate, the TOF value can be as high as 10000h -1 The above values are higher than those of most reported heterogeneous catalysts and some homogeneous catalysts.
[0061] Embodiment 6:
[0062] The DATPIM-Ru catalyst is recycled and reused in the following steps:
[0063] (1) Add 8 ml of deionized water to the system for completing the catalytic reaction of formic acid to produce hydrogen in Example 4, shake well and mix, and then centrifuge.
[0064] (2) The separated DATPIM-Ru was dissolved in a small amount of dimethyl sulfoxide solution, and then 8 ml of deionized water was added to precipitate the solid, which was then separated by centrifugation.
[0065] (3) Repeat step (2) once.
[0066] (4) Dry the solid obtained by centrifugation in step (3) in an oven at 80°C to obtain a recovered DATPIM-Ru catalyst. (5) Repeat the experiment according to Example 4 to calculate the yield and TOF value of the recycled DATPIM-Ru catalyst.
[0067] Table 2. Summary of the effects of DATPIM-Ru catalyst recycled in Example 6 on formic acid production of hydrogen
[0068]
[0069]
[0070] As shown in Table 2, the catalytic activity of the DATPIM-Ru catalyst did not decrease significantly during the four recycling cycles, the TOF remained above 9000, and the formic acid yield remained above 90%.
[0071] From the above we can know:
[0072] In the present invention, the self-microporous polymer has many advantages such as rich pore structure, high specific surface area, strong chemical modifiability, etc., and compared with other organic porous polymers, it has the unique advantage of being completely soluble in specific solvents. Ruthenium-based self-microporous polymer catalysts achieve high activity while enhancing the stability of the catalyst, and can be regenerated and recovered by dissolution and precipitation methods, realizing the complementary advantages of heterogeneous catalysts and homogeneous catalysis.
[0073] In the present invention, the coordination of ruthenium metal and the specific functional group of the self-microporous polymer realizes the unit point dispersion of ruthenium metal, which is conducive to fully utilizing the precious metal and reducing costs. The catalyst preparation method and recovery method prepared by the present invention are simple to operate, have low requirements for equipment construction, and are easy to implement and promote.
[0074] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0075] The above description enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A soluble single-site ruthenium-based self-microporous polymer catalyst, characterized in that: include: The microporous polymer carrier DATPIM and the coordinated active metal ruthenium; The DATPIM is a self-microporous polymer functionalized with 2,4-diamino-1,3,5-triazine (DAT) and has a chemical structure as shown in Formula I below: Formula I: Wherein Ru3+ coordinates with the 2,4-diamino-1,3,5-triazine (DAT) functional group in DATPIM to form a DATPIM-Ru catalyst having a chemical structure shown in the following formula II:
2. A soluble single-site ruthenium-based self-microporous polymer catalyst as claimed in claim 1, characterized in that: The DATPIM carrier is a soluble self-microporous polymer with a specific surface area of 30 to 2000 m 2 / g.
3. The soluble single-site ruthenium-based self-microporous polymer catalyst according to claim 1, characterized in that: The mass fraction of ruthenium is 1% to 3%.
4. The soluble single-site ruthenium-based self-microporous polymer catalyst according to claim 1, characterized in that: The mass fraction of ruthenium is 1.3%.
5. The method for preparing a soluble single-site ruthenium-based self-microporous polymer catalyst according to claim 1, characterized in that: The preparation method comprises: mixing a self-microporous polymer PIM-1, dicyandiamide and KOH in a mass ratio of 5:10:3, adding an appropriate amount of ethylene glycol monomethyl ether to dissolve, heating and stirring in a 423K oil bath at a speed of 500 rpm for reaction for 48 hours, cooling to room temperature, centrifuging the mixture, washing the obtained solid with hot water and hot methanol for several times respectively, placing the solid product in a 100°C oven for drying for 12 hours after solid-liquid separation, and obtaining a DATPIM orange-yellow solid; dissolving DATPIM and RuCl3·H2O in dimethyl sulfoxide, wherein the mass fraction of metal ruthenium is 1.5wt%, stirring at room temperature for 24 hours, and then removing the solvent to obtain a DATPIM-Ru catalyst.
6. The use of a soluble single-site ruthenium-based self-microporous polymer catalyst as claimed in claim 1, characterized in that: The catalyst is used for catalyzing the decomposition of formic acid to produce hydrogen. In the process of catalyzing the decomposition of formic acid to produce hydrogen, the reaction temperature is 363K, the pressure is normal, the solvent is dimethyl sulfoxide, triphenylphosphine is added, and the alkaline additive sodium formate is added.
Citation Information
Patent Citations
Method for enriching a homogenous catalyst from a process flow
CN102333593A
Amination polymer of intrinsic micro-porosity adsorbent and application thereof
CN107519849A
Hierarchical pore covalent organic framework-metal composite structure catalyst as well as preparation method and application thereof
CN115582144A
Preparation method of acidic solid catalyst
CN116462837A
Polymer with intrinsic micropores as well as preparation method and application of polymer
CN118772039A